Analisis Perencanaan Produksi Roti Untuk Memenuhi Permintaan di UD. Bunga Bakery - Meldia Ananda; Gamindra Jauhari (Universitas Katolik Musi Charitas, 2018)
Production planning can be defined as a process for producing goods in a certain period in accordance with what is predicted or scheduled through organizing resources such as labor, raw materials, machinery and other equipment. Determining the optimal number of products to be produced is the key to proper production planning. Production needs are carried out to meet demand at the minimum cost level. The purpose of this study is to estimate (predict) demand which can be used as the basis for making a production plan, by determining how many products to produce, utilizing limited resources efficiently. And increase production capacity to meet the ups and downs of demand. After forecasting by using a constant method, linear and quadratic bread, sayakaya, chocolate, coconut, blueberry, pineapple with the smallest error method, namely the standard error estimate (SEE), the constant method has the smallest error value. The next period is predicted the number of requests for sarikaya bread for 464700 packs, chocolate flavor 1390152 packs, coconut flavor 508524 packs, blueberry flavor 515112 packs, and pineapple flavor 256356 packs.